IPTEKS PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Mewo, Angelia Natashia Martina; Kalalo, Meily Yoke Betsy (Universitas Sam Ratulangi, 2018)
Regional tax is the price paid for the area being developed by the region and for the region. Regional tax realization is very influential on regional revenue (PAD). The purpose of this study is to look at tax revenues in the city in this case the Tax Management and Retribution Agency of the City of Manado. The method used is descriptive method because this study consists of explanatory words. This study gets tangible results from knowing 2016 until 2017 there has been an increase. However, there are still several types of local taxes that have decreased. Therefore, the city of Manado or BP2RD must have more or more obligations that still do not have the awareness to guide taxes, so that tax revenues / realization in the city of Manado will continue to increase.Keywords : regional tax, collection, local revenue